The causal relationship between obesity and IgA nephropathy: a Mendelian randomization study - Peng-tao Dong; Zheng Wang; Xiao-yu Li; Qing Zhang (Editorial Department of Journal of Clinical Nephrology, 2024)
ObjectiveTo explore the potential causal relationship between obesity and IgA nephropathy through Mendelian randomization. MethodsSummary-level data from genome-wide association studies of obesity-related shapes (body mass index, percentage body fat, waist circumference & waist-to-hip ratio) and IgA nephropathy were acquired. Inverse variance weighted analysis was utilized as a primary analytical method with weighted median and MR-Egger regression supplementing the results. Sensitivity analyses were performed for testing the reliability of the results of Mendelian randomization. ResultsThe results of two-sample Mendelian randomization indicated that, according to forward inverse variance weighted analysis, BMI （OR=1.193, 95%CI：1.104～1.289, P<0.001）, percentage of body fat（OR=1.189, 95%CI：1.054～1.341, P=0.005）and waist circumference （OR=1.307， 95%CI：1.178～1.450, P<0.001） might have a positive causal relationship with IgA nephropathy. Multivariate Mendelian randomization revealed no statistically significant causal association between percentage body fat (P=0.10), waist circumference (P=0.18) and IgA nephropathy. Inverse Mendelian randomization showed a positive causal relationship between IgA nephropathy and waist-to-hip ratio（OR=1.112, 95%CI：1.046～1.183, P=0.0007）and sensitivity analyses were all reliable. ConclusionsThe results of Mendelian randomization support that obesity boosts the incidence of IgA nephropathy. Individuals with high BMI should pay greater attention to weight and life management and have regular renal function tests.